2016
DOI: 10.1186/s13567-016-0354-9
|View full text |Cite
|
Sign up to set email alerts
|

Productive replication of nephropathogenic infectious bronchitis virus in peripheral blood monocytic cells, a strategy for viral dissemination and kidney infection in chickens

Abstract: In the present study, the replication kinetics of nephropathogenic (B1648) and respiratory (Massachusetts-M41) IBV strains were compared in vitro in respiratory mucosa explants and blood monocytes (KUL01+ cells), and in vivo in chickens to understand why some IBV strains have a kidney tropism. B1648 was replicating somewhat better than M41 in the epithelium of the respiratory mucosa explants and used more KUL01+ cells to penetrate the deeper layers of the respiratory tract. B1648 was productively replicating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 70 publications
(115 reference statements)
4
53
0
Order By: Relevance
“…The ability of a virus to infect and replicate in tissues beyond the site of infection depends on the route of transport and the susceptibility of a respective organ. Since the 1960s, viremia has been proposed as one of the routes of IBV dissemination [18], with only recent evidence for involvement of mononuclear cells in transportation of the virus throughout the body [19,20]. In our study, mononuclear cells expressing viral proteins were only rarely detected (data not shown), so it is yet unclear whether they truly contribute to IBV dissemination.…”
Section: Discussionmentioning
confidence: 47%
“…The ability of a virus to infect and replicate in tissues beyond the site of infection depends on the route of transport and the susceptibility of a respective organ. Since the 1960s, viremia has been proposed as one of the routes of IBV dissemination [18], with only recent evidence for involvement of mononuclear cells in transportation of the virus throughout the body [19,20]. In our study, mononuclear cells expressing viral proteins were only rarely detected (data not shown), so it is yet unclear whether they truly contribute to IBV dissemination.…”
Section: Discussionmentioning
confidence: 47%
“…Some of these factors known to exacerbate the clinical disease have been used in experimental models to evaluate the clinical outcome of interaction between such factors and different IBV strains. Reddy et al (154) reported significant differences between the replication kinetics of the nephropathogenic B1648 and respiratory M41 IBV strains when compared in vitro in respiratory mucosa explants and blood monocytes (KUL01(+) cells), and in vivo in chickens that might explain the different behavior of these strains in chickens.…”
Section: Pathogenicitymentioning
confidence: 99%
“…Interestingly, serum cMBL showed an acute response during IBV infection with an approximately two-fold increase in concentration (Juul-Madsen et al, 2011;Nielsen et al, 1998Nielsen et al, , 1999. As transport of IBV from the primary site of infection to other target organs has been suggested to occur via viremia (McFerran and McNulty, 1993;Reddy et al, 2016), it might well be that MBL is able to interact directly with IBV in the blood during transport to other target organs.…”
Section: Discussionmentioning
confidence: 99%